Perlindungan Hukum Terhadap Tenaga Kerja Indonesia yang Bekerja ke Luar Negeri (Suatu Pendekatan Ontologi, Epistemologi, Aksiologi dan Ideologi) - Solehoddin (Fakultas Hukum Universitas Mulawarman, 2009)
The job opportunities in Indonesia which are limited have impact to the increase of unemployment. In other side, the job opportunities abroad which still need a lot of employment and offer high salary are attracting Indonesian peoples to work abroad. The protection is recognition of human dignity which is aim at the equal treatment for all peoples. In this regard, it is important to formulate a concept of protection which contains some ideals of to reform, to construct, and to build. The protection of Indonesian labour abroad shall be given in all phase; pre-employment, during employment, and post employment. In the future, the ideology of legal protection for Indonesian labour abroad must imply ideals of law and legal certainty and equality.